Relationship between Risk Appetite and Investment Decisions in High-Risk Ventures in South Korea - Seung, Han (International Journal of Modern Risk Management, 2024)
Purpose: The aim of the study was to examine the relationship between risk appetite and investment decisions in high-risk ventures in South Korea. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The relationship between risk appetite and investment decisions in high-risk ventures in South Korea reveals a strong correlation where investors with higher risk tolerance are more likely to engage in high-risk ventures. These investors are driven by the potential for substantial returns, despite the associated volatility and uncertainty. The findings indicate that cultural factors, economic conditions, and market dynamics in South Korea play a significant role in shaping this risk appetite. Unique Contribution to Theory, Practice and Policy: Prospect theory, risk parity theory & behavioral portfolio theory may be used to anchor future studies of relationship between risk appetite and investment decisions in high-risk ventures in South Korea. Practically, businesses should focus on several strategies to optimize the effectiveness of their insurance coverage in managing business interruption risks.